La Acción Católica en Cuenca: de las asociaciones obreras a la “ciudadanía moral” en el primer tercio del siglo XX (Estudios) - Martínez Borrero, Juan (2017)
The development of a sense of citizenry in the province of Azuay, in Ecuador, during the first third of the twentieth century, was linked to the Catholic Action, a lay movement sponsored by the Church aimed at regaining the ground that traditional conservative society believed could be lost to the social and political changes of emerging modernity. During this period, Cuenca was being impacted by economic, social, urban, and cultural transformations, among which the most noteworthy were the opening up of trade with Europe and the resulting flow of ideas. The Catholic Action steered organized labor toward its own ideology, countering liberal concepts and the growing presence of socialist ideology. These lay persons promoted a “moral Christian citizenry” that laid the foundations for a predominantly conservative society.